Use of Gliricidia sepium and Leucaena leucocephala in alley cropping systems to improve Brazilian coastal tableland soils - Barreto, Antônio Carlos; Fernandes, Marcelo Ferreira (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to evaluate the shoot biomass of gliricidia (Gliricidia sepium) and leucaena (Leucaena leucocephala) in an alley cropping system and the addition effect of this biomass on the chemical and physical properties of a Yellow Latosol of a coastal tableland area, at Sergipe State, Brazil. The yield of cassava cultivated in the alleys of these legumes was also evaluated. Gliricidia was planted by cuttings in 1994, and leucaena was planted by seedlings in 1995, in rows of 3 m apart. At periods of three to five months, cuts were carried on and the shoot biomass was incorporated to the soil. Stems with diameter higher than 1 cm were not considered in the biomass weight. The dry matter obtained in these cuts was expressed in ton ha-1 year-1. In 1998, soil samples were taken to quantify some soil chemical and physical properties. Soil samples from a neighbor area were used as control. Leucaena and gliricidia yield were, respectively, 4.87 and 5.80 ton ha-1 year-1 of shoot dry matter. Gliricidia showed a lesser competition to cassava in the interrows. The incorporation of shoot biomass of both legumes to the soil caused an increment in the values of pH and Ca+Mg, but has not affected organic matter content and CEC. Decreases of the soil density and increases of the porosity were also observed in response to legume incorporation. These effects were most noticeable in the superficial layers.